2020
DOI: 10.1007/s10008-020-04819-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxide nanolayer formation on surface of modified blast furnace sludge particles during voltammetric cycling in alkaline media

Abstract: Knowledge of the properties of metallurgical waste is essential for the assessment of their recycling. In this work, the formation of iron oxide nanolayers during voltammetric cycling in 1 M NaOH on the particle surface of blast furnace sludge after acid leaching (BFSL) was studied. Most importantly, the effect of hydrogen on these processes was of particular interest. For these purposes, the study combines electrochemical methods, cyclic voltammetry on solid and carbon paste electrodes, with analytical optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Also, if dissolved ion species are supplied from the electrode by its reduction, the redox reaction of Fe 2+ /Fe 3+ ( E 0 = 0.77 vs SHE) is observable in this potential window. In actuality, former studies using the magnetite electrode observed the Fe 2+ /Fe 3+ redox couple on voltammograms even when ferrous or ferric ions were not added to solutions, suggesting that dissolved iron species are supplied from magnetite. …”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Also, if dissolved ion species are supplied from the electrode by its reduction, the redox reaction of Fe 2+ /Fe 3+ ( E 0 = 0.77 vs SHE) is observable in this potential window. In actuality, former studies using the magnetite electrode observed the Fe 2+ /Fe 3+ redox couple on voltammograms even when ferrous or ferric ions were not added to solutions, suggesting that dissolved iron species are supplied from magnetite. …”
Section: Resultsmentioning
confidence: 96%
“…Figure a shows CVs recorded using the magnetite electrode at 25 °C, where the potential ( E ) was scanned in the potential range, E = 0.3 → −0.5 → 0.8 → 0.3 V (vs Ag/AgCl). CV is well characterized by one redox couple (anodic peak A 1 and cathodic peak C 1 ) at E ∼ 0.4 V and one cathodic peak (C 2 ) at E ∼ −0.1 V. Former studies assigned the C 1 /A 1 couple to the redox of dissolved Fe 2+ /Fe 3+ and C 2 to the reduction of ferric ions on the surface of the magnetite crystal (Fe magn III ). Thus, dissolved Fe 2+ , which is supplied at C 2 , is oxidized to Fe 3+ at A 1 , and then, Fe 3+ is reduced at C 1 in the subsequent cathodic scan to give the C 1 /A 1 redox couple. Because dissolved iron species does not exist in the original solution, the A 1 /C 1 redox couple did not appear when the potential was initially scanned in the anodic direction, that is, E = 0.3 → 0.8 V, as shown in Figure b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once Fe(0) is formed due to hydrogen evolution at a potential of approximately − 1.5 V, the anodic peak can be observed. The presence of metallic iron was proved in 43 . When starting in the cathodic direction from 0 to − 1.5 V, a sufficient amount of Fe(II) is formed and anodic peaks also occur.…”
Section: Resultsmentioning
confidence: 99%